The Impact of the West Africa Ebola Outbreak on Obstetric Health Care in Sierra Leone - Brolin Ribacke, Kim J. (PLoS One, 2016)
BACKGROUND: As Sierra Leone celebrates the end of the Ebola Virus Disease (EVD) outbreak, we can begin to fully grasp its impact on already weak health systems. The EVD outbreak in West Africa forced many hospitals to close down or reduce their activity, either to prevent nosocomial transmission or because of staff shortages. The aim of this study is to assess the potential impact of EVD on nationwide access to obstetric care in Sierra Leone. METHODS AND FINDINGS: Community health officers collected weekly data between January 2014—May 2015 on in-hospital deliveries and caesarean sections (C-sections) from all open facilities (public, private for-profit and private non-profit sectors) offering emergency obstetrics in Sierra Leone. This was compared to official data of EVD cases per district. Logistic and Poisson regression analyses were used to compute risk and rate estimates. Nationwide, the number of in-hospital deliveries and C-sections decreased by over 20% during the EVD outbreak. The decline occurred early on in the EVD outbreak and was mainly attributable to the closing of private not-for-profit hospitals rather than government facilities. Due to difficulties in collecting data in the midst of an epidemic, limitations of this study include some missing data points. CONCLUSIONS: Both the number of in-hospital deliveries and C-sections substantially declined shortly after the onset of the EVD outbreak. Since access to emergency obstetric care, like C-sections, is associated with decreased maternal mortality, many women are likely to have died due to the reduced access to appropriate care during childbirth. Future research on indirect health effects of health system breakdown should ideally be nationwide and continue also into the recovery phase. It is also important to understand the mechanisms behind the deterioration so that important health services can be reestablished.